Broiler rabbit farming in north-eastern hills region - Bharti, P K; Kadirvel, G; Devi, Bhanita (Indian Farming, 2018)
Rabbit farming not only serve the purpose of family through availing high quality meat for consumption but also produce different byproducts like fur skin and wool, which can be important raw materials for many valuable items like purse, hand gloves, jackets or sweeter etc. Farmers can fetch a good amount of money through selling live rabbit, its meat and various byproducts in the market that could be a highly profitable enterprise to them. Thus scientific rearing of broiler rabbit is commended to improve the livelihood of the farmers and to minimize the gap between high demand and low supply of meat and its products in the market.